ANALYSIS OF FACTORS ASSOCIATED TO OVERLOAD OF CAREGIVERS OF PATIENTS WITH ALZHEIMER DISEASE - Santos, Cristiana dos (2017)
Introduction: Caregiver’s overload may culminate in the development of acute and chronic diseases and, consequently, in the use of various medications, making him/her as sick as the elderly with Alzheimer. Therefore, the assessment of the level of caregiver’s overload points a more effective direction for the professional regarding the care guidelines. Objective: To analyze the factors associated with the overload levels of caregivers of patients with Alzheimer disease, based on the Zarit Scale. Materials and methods: This is a cross-sectional study carried out with 70 caregivers. Data were collected in the dementia outpatient clinic of a tertiary hospital, by form. The Statistical Package for Social Sciences (SPSS) was used for statistical analysis. To evaluate the association between the dependent variable (overload level) and the independent variables (socioeconomic characteristics and presence of diseases and/or symptoms after being a caregiver), the tests used were chi-square and likelihood ratio. Student’s t-test was used to compare the means. Results: Association was verified between the levels of overload and the variables degree of kinship (p=0.049), schooling (p=0.029), family income and per capita income (p=0.007), if he/she has acquired disease (p=0.004) and physical symptoms after being caregiver (p=0.030). The averages of financial participation (p=0.018), family income (p<0.001) and per capita income (p<001) were higher in those with lower intensity of overload. Conclusions: The identification of factors that influence the caregiver overload subsidizes the planning of interventions for disease prevention and health promotion, while contributing to a better life quality.